WORK OF THE CONCRETE FILLED STEEL TUBE ELEMENTS ON AXIL AND ECCENTRIC TENSION: EXPERIMENTAL RESEARCH (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article gives structures of the samples, procedure for testing and experimental results at the work of the concrete filled steel tube elements in tension. It also describes character of strains development Keywords: concrete filled steel tube elements, tension, strains.